2016
DOI: 10.1160/th15-08-0631
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with rivaroxaban attenuates stroke severity in rats by a dual antithrombotic and anti-inflammatory mechanism

Abstract: Stroke outcome is more favourable in patients receiving oral anticoagulants compared with non-anticoagulated patients. The reasons for this "stroke-attenuating" property of oral anticoagulants are largely unknown. This study examined whether prestroke anticoagulation with rivaroxaban, a novel direct factor Xa inhibitor, influences stroke severity, thrombin-mediated intracerebral thrombus formation and pro-inflammatory processes in a rat model of brain ischaemia/reperfusion injury. Male Wistar rats were anticoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
8
15
0
Order By: Relevance
“…Furthermore, Rivaroxaban may have little effect on MMP-9 expression. This study also reveals that Rivaroxaban does not increase occludin degradation and has no effect on BBB stability in diabetes post-experimental ET, which is similar to normal experimental stroke models 55 .…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, Rivaroxaban may have little effect on MMP-9 expression. This study also reveals that Rivaroxaban does not increase occludin degradation and has no effect on BBB stability in diabetes post-experimental ET, which is similar to normal experimental stroke models 55 .…”
Section: Discussionsupporting
confidence: 70%
“…The latest meta-analysis of observational studies on dabigatran (not included in our analysis) corroborated these findings by pooling seven cohort studies (HR 0.44, 95 % CI 0.34–0.59, I 2  = 64 % for dabigatran 150 mg) [77]. The mechanism behind a reduced ICH risk is still largely unknown, although in vivo studies pointed out that the potential anti-inflammatory properties of dabigatran may partially explain the observed clinical benefit [78, 79]. …”
Section: Discussionsupporting
confidence: 57%
“…Clinical studies with NOACS have shown that these drugs reduce the incidence of cardiovascular events including coronary and peripheral artery disease, cerebral ischemia, thrombosis, thromboembolic events, and atherosclerosis [12,13]. In addition to this, experimental studies proposed a series of vascular protective properties of NOAC via inhibition of FXa [14][15][16][17][18][19][20][21][22][23][24][25][26]. These include potential anti-inflammatory effects [15,[19][20][21]23,24,27], that might perhaps impact vascular function and pathology [14,25].…”
Section: Introductionmentioning
confidence: 99%